FATTY ACID COMPOSITION AND ANTIOXIDANT ACTIVITY OF CAMELLIA NINHII SEED OIL COLLECTED IN LAM DONG PROVINCE - Trần, Thị Tú Quyên (Trường Đại học Đà Lạt, 2025)
The seed oil of Camellia ninhii was studied for the first time on its fatty acid composition by gas chromatography-mass spectrometry (GC-MS) and antioxidant activity by the DPPH method. The results show that unsaturated fatty acids account for the largest amount, especially oleic acid with 45.43% of the total sample analyzed. In addition, other fatty acids, palmitic, linoleic, pentadecanoic, and two aromatic acids, benzoic and cinnamic, were present. The sample of C. ninhii seed oil exhibited mild antioxidant activity against DPPH free radicals with IC50 = 0.94 mg/mL.